Peliosis lienalis with atraumatic splenic rupture in a patient with chronic myelomonocytic leukemia: A case report. (March 2021) - Widmer, Lukas Werner; Ardüser, David; Kraus, Rebecca; Gebbers, Jan-Olaf; Villiger, Peter
Highlights: Peliosis lienalis is a rare pathological entity which may be associated with chronic myelomonocytic leukemia. Increasing splenomegaly in patients with hematological malignancies should rise suspicion of impending splenic rupture. Peliosis lienalis may be suspected with new inhomogeneous splenic parenchyma on sonography. Abstract: Introduction: Atraumatic splenic rupture is a rare but life-threatening condition which may be associated with hematological malignancies. Presentation of case: We present the case of a 63-year-old male patient with a history of chronic myelomonocytic leukemia and sarcoidosis under therapy with prednisone, who suffered an atraumatic splenic rupture with hemodynamic instability. He was managed with proximal splenic artery embolization and secondary open splenectomy. On pathology the diagnosis of peliosis lienalis was established. Discussion: Peliosis is a rare pathological entity, which presents with multiple blood-filled cavities within parenchymatous organs and is of unknown etiology and pathogenesis. In retrospect a rapid increase in splenomegaly and inhomogeneous parenchyma of the spleen on sonography was realized. Conclusion: Sonographic changes in size and parenchyma of the spleen in patients with hematological malignancies might help suspecting peliosis lienalis with impending splenic rupture and could alter clinical management towards a prophylactic splenectomy.